2009
DOI: 10.1111/j.1600-0706.2009.17252.x
|View full text |Cite
|
Sign up to set email alerts
|

Biodiversity effects on productivity and stability of marine macroalgal communities: the role of environmental context

Abstract: The influence of biodiversity on ecosystem functioning has been the focus of much recent research, but the role of environmental context and the mechanisms by which it may influence diversity effects on production and stability remain poorly understood. We assembled marine macroalgal communities in two mesocosm experiments that varied nutrient supply, and at four field sites that differed naturally in environmental conditions. Concordant with theory, nutrient addition promoted positive species richness effects… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
62
3
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 74 publications
(73 citation statements)
references
References 69 publications
(127 reference statements)
5
62
3
1
Order By: Relevance
“…Both negative (Kraufvelin et al, 2010;Bracken and Williams, 2013) and positive BEF relationships have been reported within macroalgal assemblages in the context of photosynthetic carbon fixation Arenas et al, 2009;Boyer et al, 2009;Griffin et al, 2009). Although not using an experiment designed to specifically test the relationship between diversity and productivity, Kraufvelin et al (2010) observed declining primary production within increasing macroalgal species richness in temperate rocky shores (SE Norway) driven by strong identity effects associated with the resident fucoids.…”
Section: Ecosystem Process: Biomass Productionmentioning
confidence: 97%
“…Both negative (Kraufvelin et al, 2010;Bracken and Williams, 2013) and positive BEF relationships have been reported within macroalgal assemblages in the context of photosynthetic carbon fixation Arenas et al, 2009;Boyer et al, 2009;Griffin et al, 2009). Although not using an experiment designed to specifically test the relationship between diversity and productivity, Kraufvelin et al (2010) observed declining primary production within increasing macroalgal species richness in temperate rocky shores (SE Norway) driven by strong identity effects associated with the resident fucoids.…”
Section: Ecosystem Process: Biomass Productionmentioning
confidence: 97%
“…Here, we focus on biodiversity patterns in the intertidal seaweed community, exclusive of other sessile organisms, to facilitate understanding of the drivers of natural patterns in biodiversity and the functional role of seaweeds as key marine primary producers and foundation species. There is often, but not always, a positive relationship between seaweed ecosystem function and biodiversity (Allison 2004, Arenas et al 2009, Boyer et al 2009, Bracken et al 2011, Aquilino and Stachowicz 2012. In prior work, we found that both biomass and nitrogen acquisition increase with seaweed richness (Bracken and Stachowicz 2006, Stachowicz et al 2008.…”
Section: Introductionmentioning
confidence: 99%
“…Survivorship, and therefore total lifespan, is dependent on the type and quality of food (Duffy and Hay 1991, Cruz-Rivera and Hay 2000a. Given that some ovigerous females in their first or second v www.esajournals.org ovulation likely migrated into our communities via the seawater or were added as propagules, and water temperatures of ;298C during our experiment (Boyer et al 2009), we estimate 2-3 overlapping generations passed during our experiment.…”
Section: Study System: General Ecologymentioning
confidence: 99%